Design of a Mobile Application for Wireless Network Monitoring Based on Android - Mahfudzin, Abdul Halim; Widiantoko, Ari; Sudibyo, Novi Herawadi (Proceeding International Conference on Information Technology and Business, 2023)
Information and communication technology that is increasingly widespread today uses a computer network system as a medium for transforming information and data. One of the common network utilizations today is a wireless network using Wi-Fi (Wireless Fidelity) technology. The problem experienced at Junior High School Muhammadiyah 3 Metro is that the network administrator still uses a simple way of checking the network connection, namely by pinging the hosts connected to the network. The goal that the authors achieve is to monitor data traffic on wireless internet networks by designing Android applications as network controllers. With this problem, the authors made a thesis with the title